Clinical predictors for biochemical failure in patients with positive surgical margin after robotic-assisted radical prostatectomy. Issue 3 (June 2022) - Su, Shih-Huan; Chang, Ying-Hsu; Huang, Liang-Kang; Chu, Yuan-Cheng; Kan, Hung-Cheng; Liu, Chung-Yi; Lin, Po-Hung; Yu, Kai-Jie; Wu, Chun-Te; Pang, See-Tong; Chuang, Cheng-Keng; Shao, I-Hung
Objective: Patients with positive surgical margins (PSMs) after radical prostatectomy for localized prostate cancer have a higher risk of biochemical failure (BCF). We investigated the risk factors of BCF in patients with PSMs after robotic-assisted radical prostatectomy (RARP). Methods: We evaluated 462 patients who underwent RARP in a single medical center from 2006 through 2013. Of them, 61 with PSMs did not receive any treatment before BCF. Kaplan-Meier curve and Cox regression analysis were used to compare patients with (n = 19) and without (n = 41) BCF. Results: Overall, 13.2% of patients had PSMs, and of those, 31.7% experienced BCF during follow-up. The mean follow-up duration was 43.7 months (42.4 [non-BCF] vs 46.35 (BCF], p = 0.51). In univariant analyses, the platelet to lymphocyte ratio (6.26 [non-BCF] vs 8.02 [BCF], p = 0.04) differed statistically. When patients were grouped by pathologic grade ≦2 or ≧3 ( p = 0.004), the BCF-free survival rates differed significantly. Seminal vesicle invasion also differed significantly (5 [non-BCF] vs 7 [BCF], p = 0.005). Patients with undetectable nadir prostate-specific antigen (PSA) after RARP (BCF rate 4/34) differed statistically from those with detectable PSA after RARP (BCF rate 15/26) ( p < 0.001). In the multivariate analysis, the platelet/lymphocyte (P/L) ratio, pathologic grade, and undetectable nadir PSA remained statistically significant. Conclusions: In patients who undergo RARP and have PSMs, P/L ratio >9 preoperatively, pathologic grade ⩾3, and detectable nadir PSA after RARP should be considered adverse features. Early intervention such as salvage radiation therapy or androgen deprivation therapy should be offered to these patients.